An Outline of Processability Theory and Its Relationship to Other Approaches to SLA. Issue 1 (March 2015) - Pienemann, Manfred; Hulstijn, Jan H.; Ellis, Rod; Eskildsen, Søren W.
<x xml:space="preserve">Abstract</x> In this article I make the point that there has been a continuous focus on second language development in second language acquisition research for over 40 years and that there is clear empirical evidence for generalizable developmental patterns. I will both summarize some of the core assumptions of Processability Theory (PT) as an approach to explaining developmental patterns and learner variation and compare the position assumed by PT with the Dynamic Systems Theory approach proposed by de Bot, Lowie, and Verspoor and with O'Grady's processing‐based approach to Emergentism. In addition, I will summarize the Teachability Hypothesis and describe its limited relationship to PT in order to respond briefly to the article on the same issue by Zhang and Lantolf in this Special Issue.